The analysis of stages of creation and operation of scaffoldings with regard to safety of users - Błazik-Borowa, Ewa; Szer, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In the paper the five stages of „life” of scaffolding are explored: preparation of design documentation of scaffolding, selection of the set of elements to assembly a scaffolding, erection ,operation stage and the disassembling of scaffolding. Each of the stages is shown in forms of diagrams and it is analysed with regards to the possibillity of accurrance of hazardous situations. The issues analysed in this paper show how many factors, both technical (eg. in preparation - capacity estimation; performance - the use of appropriate elements) and personal (eg. accuracy in making connectors) affect the final effect which is safe erection and later use of a scaffolding.